State of vascular flora diversity from Pantanos de Villa (Lima - Peru) - Ramirez, Dámaso W. (2010)
This work shows the results of the vascular flora inventory of Pantanos de Villa carried out in 2007, also, the floristic changes of the last years are analyzed. 47 wild species have been registered, included in 43 genus and 27 families. The higher species number were found in Poaceae (7), Cyperaceae (4) and Asteraceae (4). We reported 7 wilds species as new records for the wetland: Alternanthera pubiflora, Alternanthera halimifolia, Limnobium laevigatum, Colocasia esculenta, Rumex obtusifolius, Elodea potamogeton, Plantago major. Also we found 11 cultivated species in the wetland. The results show a decrease in species richness compared with previous studies, mainly of aquatic species. Similarity analysis with previous studies indicates a change in the composition of the flora in time.